(untitled) (Swiss Medical Weekly, 2020)
We report the uncommon clinical case of our patient, an 83-year-old woman with Alzheimer disease, who acquired a potentially fatal tropical infection in an open-air swimming pool in the Alps. Chromobacterium violaceum is a rare gram-negative anaerobe bacillus, generally associated with serious waterborne infections in tropical and subtropical regions. The patient presented to our emergency department with a 2-day history of fever and a small non-necrotic wound on the right leg after a minor injury 9 days before. It turned out to be the first infection in Switzerland due to C. violaceum, a deadly bacterium typical of tropical regions. C. violaceum appeared for the first time in Europe in the 2011. This is now the third documented case in less than a year and the second autochthonous infection ever in our continent. A delay in adequate treatment of this emerging pathogen may be associated with high fatality rates.